O planejamento territorial no Brasil: efeitos da Política Nacional de Desenvolvimento Regional no Estado do Rio Grande do Sul - Antonio Paulo Cargnin; Aldomar A. Rückert (Confins)
This article aims to evaluate the territorial effects of the National Policy of Regional Development (Política Nacional de Desenvolvimento Regional – PNDR) in the State of Rio Grande do Sul, Brazil. For such purpose the policy and its instruments that have a higher incidence in the territory of state are analyzed: the Program for Promotion of Sustainability of Sub-Regional Spaces (Programa de Promoção da Sustentabilidade de Espaços Sub-Regionais – PROMESO) and the Program for the Development of the Frontier Strip (Programa de Desenvolvimento da Faixa de Fronteira – PDFF). In the following results already achieved by these programs are evaluated and possible effects on regional disparities are identified. In parallel, we try to analyze the performance of the main actors involved in the implementation of the policy.